Relationship between the Soluble F11 Receptor and Markers of Inflammation in Hemodialysis Patients. (1st April 2007) - Salifu, Moro O.; Kolff, Quirine; Murty, Preethi; Haria, Dhiren M.; Zimpa, Mahamadu; Shakeel, Muhammad; Lee, Howon; Kornecki, Elizabeth; Babinska, Anna
Abstract : Background: The human F11 receptor (F11R) is an important cell adhesion molecule implicated in inflammatory thrombosis. We hypothesize that serum levels of the soluble released form of F11R (sF11R) are elevated in dialysis patients since these patients have higher cardiovascular disease burdens than the general population. In this study, we examined whether sF11R levels were elevated in hemodialysis (HD) patients and correlated with known inflammatory cytokines. Methods: We used new and standard enzyme-linked immunosorbent assay techniques to measure levels of sF11R, as well as high-sensitivity C-reactive protein (hs-CRP), tumor necrosis factor α (TNF-α), interleukin-6 (IL-6), and interleukin-10 (IL-10), in a cross section of 52 HD patients and compared these with 15 healthy controls. Results: The mean age of the patients was 56 ± 17.3 years; 60% were female, and 36% had diabetes mellitus. Serum levels of sF11R, hs-CRP, TNF-α, IL-6, and IL-10 were all significantly higher in patients than in control sera ( p < .05). Within the patient group, there was a significant positive correlation between sF11R and TNF-α ( r = .41, p = .003), IL-10 ( r = .32, p = .023), and IL-6 ( r = .32, p = .023), whereas hs-CRP showed no significant correlation ( r = −.27, p = .052). Conclusion: We conclude that the sF11R level is elevated in HD patients and correlates with known markers of cardiovascular disease. sF11R may be a novel cardiovascular risk marker, and longitudinal studies are needed to better assess its relationship with cardiovascular disease morbidity and mortality in this population.